A Note on Credit-Worthiness Tests - Roland Kirstein; Alexander R. Neunzig (Universität des Saarlandes, Center for the Study of Law and Economics (CSLE), 1999)
Banks often have to determine the credit worthiness, i.e. the ability to repay the loan, of their customers ex-ante. According to the theory of imperfect diagnosis, it can be rational not to use an informative diagnosis result, even though it can be acquired without costs. We call this non-contingent behavior: The decision whether to grant a loan or not is independent of the diagnosis result. Hence, it can be rational to grant a loan to a particular applicant, even if the specific diagnosis result is negative. – – Banken müssen häufig vorab über die Kreditwürdigkeit ihrer Kunden entscheiden, also deren Fähigkeit, gewährte Kredite nebst Zinsen zurückzuzahlen. Gemäß der Theorie imperfekter Entscheidungen kann es rational sein, ein Signal selbst dann nicht bei der Entscheidung zu berücksichtigen, wenn es informativ und kostenlos verfügbar ist. Dieses Verhalten nennen wir "nichtkontingent": Die Entscheidung über die Kreditgewährung ist dann unabhängig vom Diagnoseergebnis. Demnach kann es sogar rational sein, einen Kredit zu gewähren, wenn das Diagnosesignal negativ ist.
Keywords: K00; G21; D81; 330; Diagnosis Theory; Imperfect Decision Making; Adverse Selection; Banks; Credit Rationing; Kreditwürdigkeit; Kreditgeschäft; Entscheidung bei Unsicherheit; Kreditrationierung; Theorie